2018
DOI: 10.1210/jc.2018-01437
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormones and Change in N-Terminal Pro–B-Type Natriuretic Peptide Levels: The Multi-Ethnic Study of Atherosclerosis

Abstract: A more androgenic sex hormone pattern was inversely associated with NT-proBNP cross-sectionally and may contribute to sex differences in NT-proBNP. Longitudinally, a more androgenic sex hormone pattern was associated with greater increase in NT-proBNP in women, which may reflect a mechanism for CVD risk after menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 50 publications
(35 reference statements)
1
38
0
Order By: Relevance
“…There are also known sex differences in natriuretic peptide biology, with "cross talk" between these peptides and sex hormones, possibly leading to a decrease in natriuretic peptide levels after the menopause. 5,[23][24][25][26][27][28] This potential relative natriuretic peptide deficiency will lead to reduced cGMP-protein kinase G (PKG) signaling. [24][25][26][27][28][29][30][31] Any reduction in cGMP-PKG signaling due to a relative natriuretic peptide deficiency may be exacerbated in postmenopausal women by of loss of alternative, estrogen-dependent, stimulation of this pathway through endothelial nitric oxide synthase activation and nitric oxide generation.…”
Section: Discussionmentioning
confidence: 99%
“…There are also known sex differences in natriuretic peptide biology, with "cross talk" between these peptides and sex hormones, possibly leading to a decrease in natriuretic peptide levels after the menopause. 5,[23][24][25][26][27][28] This potential relative natriuretic peptide deficiency will lead to reduced cGMP-protein kinase G (PKG) signaling. [24][25][26][27][28][29][30][31] Any reduction in cGMP-PKG signaling due to a relative natriuretic peptide deficiency may be exacerbated in postmenopausal women by of loss of alternative, estrogen-dependent, stimulation of this pathway through endothelial nitric oxide synthase activation and nitric oxide generation.…”
Section: Discussionmentioning
confidence: 99%
“…93 They have an important role in contemporary HF management, with BNP and its amino-terminal-peptide fragment (NT-proBNP) being the most important molecules used to diagnose (or exclude) HF in patients presenting with acute dyspnoea (Class I, Level A evidence). 2,13,86,101 In the general population, circulating levels of cardiac NPs are approximately two-fold higher in women compared with men ( Figure 3B), 26,27,44,45 [20][21][22][23][24]103,104 which may partly explain the relative cardiac NP deficiency in men. The exact mechanism through which testosterone reduces cardiac NP levels remains poorly understood, although up-regulation of neprilysin activity by testosterone may be one possible explanation.…”
Section: Unlikelymentioning
confidence: 99%
“…• Testosterone suppresses NP levels [20][21][22][23][24] • Oestrogens may increase NP levels, 25 but more data needed…”
Section: Natriuretic Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex differences in prevalence and outcomes of diastolic dysfunction and HF have been reported ( O’Meara et al, 2007 ; Meyer et al, 2013 ; Gori et al, 2014 ) and might be partially explained by withdrawal of estrogens at the time of menopause ( Merz and Cheng, 2016 ) given that functional estrogen receptors reside in the myocardium ( Mahmoodzadeh et al, 2006 ). Indeed, myocardium remodeling can result from pathways involving sex hormones and the natriuretic peptide system, which modulates diastolic dysfunction and HF ( Hong et al, 1992 ; Maffei et al, 2001 ; Lam et al, 2011 ; Goncalves et al, 2017 ; Subramanya et al, 2018 ; Ying et al, 2018 ). However, comorbidities ( Abramov et al, 2011 ; Paulus and Tschöpe, 2013 ) and age ( Loffredo et al, 2014 ) also affect cardiac function and could explain the differences observed in several patient studies.…”
Section: Introductionmentioning
confidence: 99%